Relación entre control en el trabajo y la satisfacción laboral en el personal de la salud - Rodriguez Mariategui D’Ornellas, Cristina Pilar (2021)
Health care workers’s population characterizes by constantly being exposed to stress, and some organizational factors, such as job control and job satisfaction which play an important role in the quality of service and the perception of burnout. Therefore, the aim of this research is to identify the relationship between job control or job autonomy and job satisfaction. In order to this, a review has been performed, specifying the inclusion, exclusion and search strategy criteria, in which 805 articles were reviewed in scientific databases Scopus, Ebsco and Proquest, and 9 of them were selected for subsequent analysis. The results indicate that the relationship between both variables is mostly positive and statistically significant. Promoting control at work contributes to develop autonomy in workers and the responsibility to assume their own decisions.